COMPETITOR LOCALIZATION AND INNOVATION ACTIVITY OF PERIPHERAL INDUSTRIAL SYSTEMS IN POLAND - Świadek, Arkadiusz (Ekonomia i Prawo. Economics and Law, 2013)
Spatial proximity to competitors is an important factor in the acceleration of technological change in industrial systems in most developed countries, but is it also in Poland? The main objective of the study was to identify and evaluation the impact of distance from the nearest competitor on the innovative activity of selected peripheral regional industrial systems in Poland. Surveys conducted in the years 2007-11, including a group of 1 860 industrial companies in the five diverse and located in different parts of the country regions. Methodical analysis was based on the theory of probability – probit modeling.